Luxembourg : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Luxembourg. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Luxembourg's strong growth supported by the competitive advantages of fiscal stability, a qualified workforce, and business-friendly regulations and oversight. Economic growth reached 4.2 percent in 2016, well above the EU, and was driven by net exports of financial services. Growth is projected at 3.8 percent in 2017, with continued strong job creation and a pickup in inflation. Growth prospects are good but subject to downside risks, including a retreat from cross-border integration and policy uncertainty in the United States and related to Brexit and coming elections in Europe. These could result in financial market volatility affecting the financial system.